Possibility of stevia (Stevia rebaudiana B.) production in Hungary - Takácsné Hájos, M.; Rubóczki, T.; Kiss, A. (International Journal of Horticultural Science, 2016)
Artificial sweeteners have harmful effect on human health, so it is great interested in stevia extract. Our experiment was aimed to show the possibility of inland production of stevia. Different plastic mulches were used (black and white) on raised bed and were compared to uncovered (control) plots for yield and state of health of plants. Furthermore we evaluated the depth of cuttings (low cutting until the 6th double leaf; normal cutting until the upper ⅓ of the plant) on the yield depending on the covering method. The plants were transplanted on 9 of May, 2014 on raised bed, 3 rows on it, with 33x25 cm spacing. According to our results, the black plastic mulch produced the highest yield, which can be explained by suppressing effect on weeds, furthermore it kept the soil warm, moist and protected the lower leaves from soil wetness. But, the white sheet mulch could not eliminate weeds around the plants. The total biomass on the black plastic sheet covered plots was the highest, nearly 1000 g pro plant by low cutting. On the control plots the fungi infection reached about 25-30%, which caused leaf falling of plants, decreasing of yield by the end of vegetation period. To summarise, stevia production is possible in Hungary, but it is important to pay attention to the balanced soil moisture and low humidity in the leaf area. It is suggested to cover the soil with plastic sheet or organic materials, such as bark and chippings.